Natural disasters and firm leasing: A collateral channel - Wang, Jiawei (Brooke) (Journal of corporate finance (Amsterdam, Netherlands), 2023)
This paper studies the role of lease financing in disaster-affected firms under collateral constraints. Disaster-affected firms demand funds for post-disaster reconstruction. However, the destruction of natural disasters leads to collateral constraints, which create external financing frictions. I find that affected firms obtain financing through operating leases after natural disasters. The significance of the findings highlights the importance of operating leases for collateral-constrained firms.